Review and perspective on encrypted traffic identification research - Wu-bin PAN; Guang CHENG; Xiao-jun GUO; Shun-xiang HUANG (Tongxin xuebao)
Considering the importance of encrypted traffic identification technology and existing research work,first,the type of encrypted traffic identification according to the demand of traffic analysis were introduced,such as protocols,applications and services.Second,the encrypted traffic identification technology was summarized,and identification technology was compared from multiple views.Third,the deficiencies and the affecting factors of the existing encrypted traffic identification technologies were induced,such as tunneling,traffic camouflage technology,new protocols of HTTP/2.0 and QUIC.Finally,prospect trends and directions of future research on encrypted traffic identification were discussed.